The comprehensive researcher development framework (CRDF): Core learning outcomes for research training - Janet L. Branchaw; Amanda R. Butz; Joseph C. Ayoob (PLoS ONE, 2025)
Becoming a researcher involves the iterative development of deep disciplinary knowledge, specific technical skills, and psychosocial attitudes, behaviors, and beliefs. Consequently, training researchers is resource- and time-intensive. In addition, expectations can be opaque because the traditional apprenticeship model used in research training is idiosyncratic, defined by norms and traditions that vary across disciplines. To align and make research training expectations more transparent, we developed the Comprehensive Researcher Development Framework (CRDF) by extracting and analyzing learning outcomes from 56 previously published evidence-based frameworks from across disciplines. The individual frameworks each addressed a limited range of training stages (e.g., undergraduate only), focused on a subset of learning outcomes (e.g., technical skills), and/or included a single or narrow subset of disciplines (e.g., biomedical sciences). The CRDF derived from these frameworks includes 79 core learning outcomes nested under 8 areas of researcher development that are supported by evidence of content validity collected from experts in the research community. The CRDF builds consensus across disciplines and addresses undergraduate through postdoctoral career stages to define a coherent continuum of research learning outcomes that can be used to monitor and study researcher development. The CRDF does not replace existing discipline-based or training stage specific frameworks but rather can link and coordinate their use. The CRDF can be used by research training program directors to design new or refine existing research training programs, track individual research mentee development over time, and demystify the research training process for mentors and mentees. The CRDF can also be used by scholars studying researcher development to link data on core learning outcomes across research training programs, stages, and disciplines.